The correlation between root canal patterns and interorificial distance in mandibular first molars - MUMCU, GONCA; KARTAL, NEVİN; CİMİLLİ, ZÜHRE HALE (My University, 2006)
Objectives: The aim of this study was to investigate the relationship of the distance between mesiobuccal (MB) and mesiolingual (ML) orifices (interorificial distances) in the pulp chamber floor and the degree of canal curvature in the mandibular first molars. Study design: In this in vitro study, 102 extracted teeth were radiographed in both buccolingual (CV) and mesiodistal (PV) directions and then grouped according to the Vertucci classification. The interorificial distance was measured by the stereomicroscope method. Results: The interorificial distance was significantly higher in type IV compared to type II (P= .016). In the logistic regression analysis, the increase in the degree of primary canal curvature of the ML in CV was a predictive factor for increase in the primary curvature of ML in PV (P = .01). Conclusion: The interorificial distance in the pulp chamber floor and primary curvatures in CV were found to be key factors for evaluation of root canal patterns in PV. © 2006 Mosby, Inc. All rights reserved.